2009
DOI: 10.1093/eurheartj/ehp337
|View full text |Cite|
|
Sign up to set email alerts
|

Guidelines for pre-operative cardiac risk assessment and perioperative cardiac management in non-cardiac surgery

Abstract: The content of these European Society of Cardiology (ESC) Guidelines has been published for personal and educational use only. No commercial use is authorized. No part of the ESC Guidelines may be translated or reproduced in any form without written permission from the ESC. Permission can be obtained upon submission of a written request to Oxford University Press, the publisher of the European Heart Journal and the party authorized to handle such permissions on behalf of the ESC.Disclaimer: The ESC Guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(97 citation statements)
references
References 239 publications
0
87
0
10
Order By: Relevance
“…However, we still perform TTE routinely which is contrary to guidelines [2,12]. Despite this, we showed that pre-transplant echocardiograms strongly predicted major clinical events after transplantation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, we still perform TTE routinely which is contrary to guidelines [2,12]. Despite this, we showed that pre-transplant echocardiograms strongly predicted major clinical events after transplantation.…”
Section: Discussionmentioning
confidence: 81%
“…Stress echocardiography or myocardial perfusion scans may be recommended [2,3] if the exercise test is positive or equivocal while coronary angiography may be considered if the functional tests show evidence of ischaemia [2]. However, Aalten et al [10] showed no evidence that pre-transplantation revascularisation improved outcome and concluded that cardiac investigation should be reserved for those with significant cardiac symptoms or high cardiac risk and poor exercise capacity as recommended for other types of surgery [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with primary and secondary hepatic tumors were included. Patients with preoperative serum creatinine >1.3 mg/dL were excluded, as kidney impairment is an independent risk factor for perioperative adverse events [14]. Based on these criteria, 172 patients in group A and 168 patients in group B were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Amerikos ir Europos širdies asociacijų gairėse nurodoma, kad net ir operacijos metu aspirino vartojimo nutraukti nereikėtų, jei kardiovaskulinių įvykių tikimybė yra ryškiai didesnė nei kraujavimo. Jei reikia, aspirino vartojimą galima nutraukti likus trims dienoms prieš invazinę procedūrą, klopidogrelio ar tikagrelolio vartojimą nutraukti likus penkioms, prasugrelio septynioms dienoms prieš planuojamą intervenciją [9,10].…”
Section: Tyrimo Objektas Ir Metodikaunclassified